2019
DOI: 10.3390/ijerph16091558
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination and Uptake of Dental Services among American Adults

Abstract: This study examined the relationship between racial discrimination and use of dental services among American adults. We used data from the 2014 Behavioral Risk Factor Surveillance System, a health-related telephone cross-sectional survey of a nationally representative sample of adults in the United States. Racial discrimination was indicated by two items, namely perception of discrimination while seeking healthcare within the past 12 months and emotional impact of discrimination within the past 30 days. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 33 publications
3
45
1
1
Order By: Relevance
“…Although our estimate is limited to adults only, the percentage is very close to the Healthy People 2020 target (61.2%) for all diabetic individuals aged 2 years or older [ 13 ]. However, our figure is lower than that previously reported for the adult US population in 2011–2014 (66%) and 2014 (68%) [ 22 , 23 ]. This finding is not unexpected, as prior studies have also reported lower compliance among diabetic individuals compared to the general population [ 24 ].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Although our estimate is limited to adults only, the percentage is very close to the Healthy People 2020 target (61.2%) for all diabetic individuals aged 2 years or older [ 13 ]. However, our figure is lower than that previously reported for the adult US population in 2011–2014 (66%) and 2014 (68%) [ 22 , 23 ]. This finding is not unexpected, as prior studies have also reported lower compliance among diabetic individuals compared to the general population [ 24 ].…”
Section: Discussioncontrasting
confidence: 97%
“…However, income was not linked to compliance in rural populations after adjusting for other factors. Having lower education or no health insurance coverage were associated with lower odds of dental compliance, as expected based on prior studies of both the diabetic and the general population [18,23]. Notably, the links between dental visits compliance and education or health insurance were more pronounced among rural diabetic residents.…”
Section: Plos Onesupporting
confidence: 79%
“…In so doing, they ignore gender and miss the opportunity to understand how inequalities are experienced by different intersections (eg being a male, White, newly arrived immigrant in the UK subjected to discrimination). Finally, Sabbah et al 42 analysed data from the 2014 U.S. Centers for Disease Control and Prevention Behavioral Risk Factor Surveillance System (BRFSS) to test associations between racial discrimination and use of dental services. This study used hierarchical logistic models to disentangle and exclude what were theorized as “confounders”: gender, race and ethnicity.…”
Section: What Do We Know About the Application Of Intersectionality Imentioning
confidence: 99%
“…According to the results, favoritism is another dimension of discrimination in health care and a barrier to justice in providing medical services. In many countries, according to the patient rights charter, patients have the right to receive full medical services irrespective of ethnicity, culture, language, type of disease, and gender (46) while the present study participants had experienced ethnicity as one of the dimensions of discrimination in health care. Discrimination based on ethnicity and the individual's origin is one of the most common forms of discrimination in health care and has been addressed in numerous studies (47)(48)(49).…”
Section: Discussionmentioning
confidence: 94%